Remote driving of multiple magnetic domain walls due to topological interaction - Purnama, I. (2014)
We present a method to drive multiple domain walls in the absence of direct current application in a coupled nanowire system. The domain walls were driven by a combination of remote coupling and exchange repulsion force from the domain wall compressions. The domain walls were compressed as they were unable to annihilate each other due to having similar topological charges. The compressions are present between the subsequent domain walls, which allow them to be driven as a group in the coupled nanowire system.